Toxicoproteomics -- a new preclinical tool. - Bandara, L; Kennedy, S (2002)
The publication of the human genome has presented the scientific community with an unprecedented amount of genetic information with the potential to revolutionize the drug discovery process. This information could be used to identify novel drug targets and disease markers or could aid in the development of personalized medicines. The realization that genetic changes must ultimately influence protein function has pushed the field of proteomics further into the limelight. In this review the applications of proteomics to the field of toxicology will be discussed. It is anticipated that, in the future, toxicologists will apply a range of genomic and proteomic techniques to address issues in toxicity.